Option pricing using Monte Carlo methods - Waldeckerová, Naďa; Witzany, Jiří, 1966-; Vacek, Vladislav; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
This thesis aims to analyse different Monte Carlo methods when applied to the problem of option pricing. Closer attention is paid to three variance reduction techniques, namely control variathes, importance sampling and antithetic variables, and two different approaches, least-squares Monte Carlo and quasi-Monte Carlo methods. The detailed analysis of the differences and improvements is done on a problem of plain vanilla option pricing. At the end the methods are each applied to valuation of different exotic options.
Vedoucí práce: Jiří Witzany
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses